Asynchronous Subthreshold CMOS Event Detector for Wireless BAN Sensor Nodes - Grimminger, Florian; Kowalczyk, G.; Unterassinger, H.; Schwarzmeier, Andre; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE BioWireleSS, 2013)
This work presents the implementation of an asynchronous event detector circuit by applying subthreshold standard cells. The presented circuit operates in an on-chip power management unit (PMU) of a wireless sensor node. Such an application demands an ultra-low power architecture for an increased overall lifetime of the sensor node. The asynchronous circuit architecture and its subthreshold logic implementation both significantly reduce the leakage power dissipation by factor three. The presented event detector is realized in a 130 nm CMOS process with regular transistors operating from a 200 mV supply voltage.
elib2cris::1512001600,grimminger2013
Keywords: Subthreshold; Asynchronouse; Event detector; Wireless sensor node

Optimum Transistor Sizing for Low-Power Subthreshold Standard Cell Designs - Grimminger, Florian; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (International Semiconductor Conference Dresden Grenoble, 2012)
This paper presents a simple method for standard cell optimization in the subthreshold regime. Through proper dimensioning of the transistor length and width an improved symmetric propagation delay and a reduction in dynamic power consumption compared to conventional CMOS standard cell implementations is achieved. The performance of the presented cells has been verified using logic gate arrays and ring oscillators with high number of stages. The measurement results reasonably agree with simulation data.
elib2cris::1512001600,grimminger2012

Subthreshold-Standardzellen für Ultra Low Power-Wakeup-Schaltungen in drahtlosen Sensorknoten - Grimminger, Florian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Wireless integrated sensor nodes for indoor monitoring and localization (invited) - Kissinger, Dietmar; Schwarzmeier, Andre; Grimminger, Florian; Mena-Carrillo, Juan; Weber, Werner; Hofer, Günter; Fischer, Georg; Weigel, Robert (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2015)
elib2cris::1512001600,kissinger2015